The Prevalence of Canine Oral Protozoa and Their Association with Periodontal Disease. (18th September 2016) - Patel, Niran; Colyer, Alison; Harris, Steve; Holcombe, Lucy; Andrew, Peter
Abstract: Periodontal disease is one of the most important health concerns for companion animals. Research into canine forms of periodontitis has focused on the identification and characterization of the bacterial communities present. However, other microorganisms are known to inhabit the oral cavity and could also influence the disease process. A novel, broad spectrum 18S PCR was developed and used, in conjunction with next‐generation sequencing analyses to target the identification of protists. Trichomonas sp. and Entamoeba sp. were identified from 92 samples of canine plaque. The overall prevalence of trichomonads was 56.52% (52/92) and entamoebae was 4.34% (4/92). Next‐generation sequencing of pooled healthy, gingivitis, early‐stage periodontitis, and severe periodontitis samples revealed the proportion of trichomonad sequences to be 3.51% (health), 2.84% (gingivitis), 6.07% (early periodontitis), and 35.04% (severe periodontitis), respectively, and entamoebae to be 0.01% (health), 0.01% (gingivitis), 0.80% (early‐stage periodontitis), and 7.91% (severe periodontitis) respectively. Both genera of protists were statistically associated with plaque from dogs with periodontal disease. These findings provide the first conclusive evidence for the presence of oral protozoa in dog plaque and suggest a possible role for protozoa in the periodontal disease process.